Upaya Meningkatkan Kinerja Pegawai Melalui Kepemimpinan Transaksional dan Pengembangan Karier - Dwi Putranti, Honorata Ratna; Harianti, Agustina Eny (E-Bisnis : Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
This study aims to determine the effect of transactional leadership and employee career development at the Ditreskrimsus Polda Central Java. The population used in this study were all employees who worked as many as 70 respondents, with proportional stratified random sampling. The source of the data used is primary data, with the data collection method using a questionnaire. The data analysis technique used is multiple linear regression analysis. The results of linear analysis state that transactional leadership and career development have a positive effect on employee performance. The value of the coefficient of determination and career development can explain the variation in employee performance variables of 58.3%. The results of the hypothesis using statistical tests are obtained that transactional leadership has a positive and significant effect on employee performance and career development which is positive and significant on employee performance.